Feasible Descent Algorithms for Mixed Complementarity Problems - Munson, Todd; Kanzow, Christian; Ferris, Michael (My University, 1998)
In this paper we consider a general algorithmic framework for solving nonlinear mixed complementarity problems. The main features of this framework are: (a) it is well-defined for an arbitrary mixed complementarity problem, (b) it generates only feasible iterates, (c) it has a strong global convergence theory, and (d) it is locally fast convergent under standard regularity assumptions. This framework is applied to the PATH solver in order to show viability of the approach. Numerical results for an appropriate modification of the PATH solver indicate that this framework leads to substantial computational improvements.
Keywords: feasible descent methods; superlinear convergence; global convergence; mixed complementarity problems